Development of a Web-Based Radiology Administration and Archiving Information System to Improve Radiology Services at Diponegoro National Hospital - Barra Putra Danuwarika; Gatot Murti Wibowo; Ahmad Hariri; Edy Susanto; Sri Mulyati (Asosiasi Riset Ilmu Kesehatan Indonesia, 2026)
Background: Challenges in conventional radiology services, such as long queues and manual administrative procedures, hinder the efficiency of radiology services. With the introduction of a web-based administrative and archiving information system, it is hoped that patient registration, examination recording, and the delivery of results can be carried out effectively and efficiently. Research Objective: To design and evaluate the impact of a web-based radiology administration information system on a suitable radiology department so that it can replace the existing manual administration system in the radiology department. Method: Using the Research and Development (R&D) method and Rapid Application Development (RAD), the system was functionally tested via Blackbox Testing (Equivalence Partitioning technique) and its satisfaction level was measured using the End User Computing Satisfaction (EUCS) method. Results: Expert validation results showed that out of 89 test cases, 85 were deemed valid, achieving a validity rate of 95.5%. Furthermore, user satisfaction testing indicated that respondents were satisfied with the system’s content, accuracy, format, ease of use, and timeliness. Conclusion: this information system is capable of addressing service issues and reducing the potential for data input errors as it is fully integrated, covering medical records, administration, examinations, and the retrieval of patient results.